Epigenetic regulation of the cannabinoid receptor CB1 in an activity‐based rat model of anorexia nervosa. Issue 5 (10th April 2020) - D'Addario, Claudio; Zaplatic, Elizabeta; Giunti, Elisa; Pucci, Mariangela; Micioni Di Bonaventura, Maria Vittoria; Scherma, Maria; Dainese, Enrico; Maccarrone, Mauro; Nilsson, Ida A.; Cifani, Carlo; Fadda, Paola
Abstract: Objective: Both environmental and genetic factors are known to contribute to the development of anorexia nervosa (AN), but the exact etiology remains poorly understood. Herein, we studied the transcriptional regulation of the endocannabinoid system, an interesting target for body weight maintenance and the control of food intake and energy balance. Method: We used two well‐characterized animal models of AN: (a) the activity‐based anorexia (ABA) model in which rats, housed with running wheels and subjected to daily food restriction, show reductions in body weight and increase in physical activity; (b) the genetic anx/anx mouse displaying the core features of AN: low food intake and emaciation. Results: Among the evaluated endocannabinoid system components, we observed a selective and significant down‐regulation of the gene encoding for the type 1 cannabinoid receptor ( Cnr1 ) in ABA rats' hypothalamus and nucleus accumbens and, in the latter area, a consistent, significant and correlated increase in DNA methylation at the gene promoter. No changes were evident in the anx/anx mice except for a down‐regulation of Cnr1, in the prefrontal cortex. Discussion: Our findings support a possible role for Cnr1 in the ABA animal model of AN. In particular, its regulation in the nucleus accumbens appears to be triggered by environmental cues due to the consistent epigenetic modulation of the promoter. These data warrant further studies on Cnr1 regulation as a possible target for treatment of AN.